The Effect of Individual, Environmental and Entrepreneurial Behavior Factors on Business Performance of Cassava SMEs Agroindustry in Padang City - Reza Mardhiyah Amir; Burhanuddin Burhanuddin; Wahyu Budi Priatna (School of Business, IPB University (SB-IPB), 2018)
The purpose of this research was to analyze the effect of individual factors, enviromental factors, entrepreneurial behavior on business performance of cassava SMEs agroindustry in Padang. This research was conducted in January-March 2017, and the number of respondents was 53 entrepreneurs. The analysis method used was quantitative analysis using Partial Least Square (PLS) version 2.0. The results showed individual factors have positive and significant effect on entrepreneurial behavior with the influence coefficient 0.430. The most dominant individual factor that reflected entrepreneurial behavior was the experience with the load factor (λ) 0.877. Environmental factors have a positive and significant effect on individual factors with the influence coefficient 0.478. Environmental factors have a positive and significant effect on entrepreneurial behavior with the influence coefficient 0.405. The most dominant environmental factor that affected entrepreneurial behavior was training with the load factor (λ) 0.840. The entrepreneurial behavior factor has a positive and significant effect on business performance with influence coefficient 0.575. The most dominant entrepreneurial behavior that influenced the business performance was the innovativeness with the load factor (λ) 0.774.Keywords: individual factor, environmental factor, entrepreneurial behavior, business performance, partial least square (PLS)